Association between Parent and Child Dietary Sodium and Potassium Intakes as Assessed by 24-h Urinary Excretion - Service, Carrie (Nutrients, 2016)
The aim of this study was to assess the association between parent and child sodium (Na) and potassium (K) intake as assessed by 24-h urinary excretion (24hUE). Primary school children and their parent(s) provided one 24-h urine sample and information on cooking and children’s discretionary salt use. Valid urine samples were provided by 108 mothers (mean age 41.8 (5.1) (SD) years, Na 120 (45) mmol/day) (7.0 g/day salt equivalent) and 40 fathers (44.4 (4.9) years, Na 152 (49) mmol/day (8.9 g/day salt), and 168 offspring (51.8% male, age 9.1 (2.0) years, Na 101 (47) mmol/day (5.9 g/day salt). When adjusted for parental age, child age and gender a 17 mmol/day Na (1 g/day salt) increase in mother’s 24hUE was associated with a 3.4 mmol/day Na (0.2 g/day salt) increase in child’s salt 24hUE (p = 0.04) with no association observed between father and child. Sixty-seven percent of parents added salt during cooking and 37% of children added salt at the table. Children who reported adding table salt had higher urinary excretion than those who did not (p = 0.01). The association between mother and child Na intake may relate to the consumption of similar foods and highlights the importance of the home environment in influencing total dietary sodium intake.